Functional diversification in the Nudix hydrolase gene family drives sesquiterpene biosynthesis in Rosa × wichurana. (22nd July 2020) - Sun, Pulu; Dégut, Clément; Réty, Stéphane; Caissard, Jean‐Claude; Hibrand‐Saint Oyant, Laurence; Bony, Aurélie; Paramita, Saretta N.; Conart, Corentin; Magnard, Jean‐Louis; Jeauffre, Julien; Abd‐El‐Haliem, Ahmed M.; Marie‐Magdelaine, Jordan; et al.
SUMMARY: Roses use a non‐canonical pathway involving a Nudix hydrolase, RhNUDX1, to synthesize their monoterpenes, especially geraniol. Here we report the characterization of another expressed NUDX1 gene from the rose cultivar Rosa x wichurana, RwNUDX1‐2 . In order to study the function of the RwNUDX1‐2 protein, we analyzed the volatile profiles of an F1 progeny generated by crossing R. chinensis cv. 'Old Blush' with R . x wichurana . A correlation test of the volatilomes with gene expression data revealed that RwNUDX1‐2 is involved in the biosynthesis of a group of sesquiterpenoids, especially E, E ‐farnesol, in addition to other sesquiterpenes. In vitro enzyme assays and heterologous in planta functional characterization of the RwNUDX1‐2 gene corroborated this result. A quantitative trait locus (QTL) analysis was performed using the data of E, E ‐farnesol contents in the progeny and a genetic map was constructed based on gene markers. The RwNUDX1‐2 gene co‐localized with the QTL for E, E ‐farnesol content, thereby confirming its function in sesquiterpenoid biosynthesis in R . x wichurana . Finally, in order to understand the structural bases for the substrate specificity of rose NUDX proteins, the RhNUDX1 protein was crystallized, and its structure was refined to 1.7 Å. By molecular modeling of different rose NUDX1 protein complexes with their respective substrates, a structural basis for substrate discrimination by rose NUDX1 proteins is proposed. Significance Statement: In rose petals, the biosynthesis of major monoterpene scent compounds involves the Nudix hydrolase RhNUDX1. Using a combination of molecular and genetic approaches, we characterize the novel RwNUDX1‐2 protein from Rosa x wichurana, which is involved in the biosynthesis of sesquiterpenoid scent compounds, and we provide structural bases for its peculiar substrate specificity.